Perancangan Dan Implementasi Aplikasi Steganografi Gambar Berbasis GUI Untuk Keamanan Pesan - Fijri Ahmad Yasin; Rahman Shobirin; Alwandi Hakim; Muhammad Hamdan Quddri Lubis (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2026)
Steganography is one of the information hiding techniques aimed at maintaining message confidentiality by embedding secret data into digital media without causing noticeable visual changes. This research focuses on the design and implementation of an image steganography application with a Graphical User Interface (GUI) that enables users to embed and extract secret text messages from digital images easily and practically. The Least Significant Bit (LSB) method is employed as the main approach, where message bits are inserted into the least significant bits of image pixels without significantly altering the visual quality of the stego-image. The development stages include requirement analysis, system design, interface design, application implementation using the Python programming language, and functional testing of message embedding and extraction features. Experimental results show that the application is able to embed text messages into digital images successfully and the hidden messages can be retrieved correctly without data loss. In addition, the stego-images do not exhibit noticeable visual differences compared to the original images, indicating that the embedded messages are not easily detected. Therefore, the developed application is considered effective as a supporting tool for maintaining message confidentiality in digital communication.